2022
DOI: 10.1002/andp.202200266
|View full text |Cite
|
Sign up to set email alerts
|

Tunneling in a Rippled Graphene Superlattice with Spin Dependence and a Mass Term

Abstract: The insertion of the band gap 𝚫 in a rippled graphene superlattice leads to new outcomes, as demonstrated. The essential thing is the appearance of opposite-spin transmissions, which increases with 𝚫 and vanishes without it. Furthermore, compared to the 𝚫 = 0 scenario, the duration of the suppression of the transmission with the same spin is longer, with many peaks. The maximum value of transmissions with the same spin declines and remains around unity. Furthermore, for particular energy values, a shift in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As a result, the spin filtering effect, which is very small in a single corrugation, becomes important with several corrugations. We previously demonstrated that corrugated graphene subjected to an external mass term modifies the tunneling effect [20,21]. In particular, it is found that resonances appear in reflection with the same spin, thus backscattering with a spin-up/-down is not null in ripple and transmission filtering becomes crucial.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the spin filtering effect, which is very small in a single corrugation, becomes important with several corrugations. We previously demonstrated that corrugated graphene subjected to an external mass term modifies the tunneling effect [20,21]. In particular, it is found that resonances appear in reflection with the same spin, thus backscattering with a spin-up/-down is not null in ripple and transmission filtering becomes crucial.…”
Section: Introductionmentioning
confidence: 99%